Primary Total Knee Arthroplasty 2018
DOI: 10.5772/intechopen.73645
|View full text |Cite
|
Sign up to set email alerts
|

Methods of DVT Prophylaxis after Total Knee Arthroplasty

Abstract: Postoperative deep-vein thrombosis (DVT), venous thromboembolism (VTE), and pulmonary embolism are few of the most serious complications following total joint arthroplasty. Identification of risk factors and initiation of prophylactic measures are the most important measures to prevent the occurrence of DVT. Several protocols and guidelines are published for DVT prophylaxis in TKA, leaving the surgeon still perplexed. Pharmacological and mechanical prophylaxis methods are used to reduce the risk of postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The impact of preoperative mobilization status on deep vein thrombosis (DVT) outcomes following total knee arthroplasty (TKA) is significant [29][30][31]. Patients who are partially or fully functionally dependent or require active support face challenges with mobility, leading to prolonged periods of immobilization and increased DVT risk post-TKA [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of preoperative mobilization status on deep vein thrombosis (DVT) outcomes following total knee arthroplasty (TKA) is significant [29][30][31]. Patients who are partially or fully functionally dependent or require active support face challenges with mobility, leading to prolonged periods of immobilization and increased DVT risk post-TKA [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of preoperative mobilization status on deep vein thrombosis (DVT) outcomes following total knee arthroplasty (TKA) is significant [29][30][31]. Patients who are partially or fully functionally dependent or require active support face challenges with mobility, leading to prolonged periods of immobilization and increased DVT risk post-TKA [29][30][31]. Our study revealed that being partially or completely dependent on preoperative mobilization can elevate DVT risk by a factor of 5, emphasizing the need for interventions like physical therapy and early ambulation programs to mitigate this risk among vulnerable TKA patients [32,33].…”
Section: Discussionmentioning
confidence: 99%